Fine tuning of the photosystem II major antenna mobility within the thylakoid membrane of higher plants - Daskalakis, Vangelis; Papadatos, Sotiris; Kleinekathöfer, Ulrich (My University, 2019)
Depending on the amount of light, the photosystem II (PSII) antennae or Light Harvesting Complexes (LHCII) switch between two states within the thylakoid membranes of higher plants, i.e., a light-harvesting and a photoprotective mode. This switch is co-regulated by a pH gradient (ΔpH) across the membrane and the interaction with the PSII subunit S (PsbS) that is proposed to induce LHCII aggregation. Herein we employ all-atom and coarse-grained molecular simulations of the major LHCII trimer at low and excess ΔpH, as well as in complexation with PsbS within a native thylakoid membrane model. Our results demonstrate the aggregation potential of LHCII and, consistent with the experimental literature, reveal the role of PsbS at atomic resolution. PsbS alters the LHCII-thylakoid lipid interactions and restores the LHCII mobility that is lost in the transition to photoprotective conditions (low lumenal pH). In agreement with this finding, diffusion of the integral membrane protein LHCII is dependent on both, electrostatic interactions and hydrophobic mismatch, while it does not obey the Saffman–Delbrück diffusion model.
Keywords: Light harvesting complex; Photoprotection; Protein diffusion; PsbS; Saffman–Delbrück model; Thylakoid lipids